2008
DOI: 10.1152/ajpcell.00454.2007
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracellular superoxide in neutrophil activation: interactions between xanthine oxidase and TLR4 induce proinflammatory cytokine production

Abstract: Reactive oxygen species (ROS) contribute to neutrophil activation and the development of acute inflammatory processes in which neutrophils play a central role. However, there is only limited information concerning the mechanisms through which extracellular ROS, and particularly cell membrane-impermeable species, such as superoxide, enhance the proinflammatory properties of neutrophils. To address this issue, neutrophils were exposed to superoxide generating combinations of xanthine oxidase and hypoxanthine or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 45 publications
0
67
0
4
Order By: Relevance
“…(46) The association of TLR-4 with xanthine oxidase was previously shown to result in neutrophil activation by superoxide. (25) In our study, we found that superoxideinduced NET formation does not occur in TLR-4 KO neutrophils. Our finding builds upon the previous discovery that oxidants enhance TLR-4 signaling in innate immune cells, specifically macrophages.…”
Section: Disclosurementioning
confidence: 42%
See 2 more Smart Citations
“…(46) The association of TLR-4 with xanthine oxidase was previously shown to result in neutrophil activation by superoxide. (25) In our study, we found that superoxideinduced NET formation does not occur in TLR-4 KO neutrophils. Our finding builds upon the previous discovery that oxidants enhance TLR-4 signaling in innate immune cells, specifically macrophages.…”
Section: Disclosurementioning
confidence: 42%
“…To determine the NET-inducing effect on neutrophils, we utilized xanthine oxidase and its substrate hypoxanthine to generate superoxide. (25) When neutrophils form NETs, decondensed chromatin studded with various proteins is expelled to form distinctive extracellular web-like structures. (3,4) We visualized this process by immunofluorescence after treatment of purified neutrophils in culture with superoxide.…”
Section: Superoxide Induces Neutrophil Extracellular Trapsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent data suggest that different ROS may have distinct effects on cellular activation. For example, whereas exposure to superoxide appears to increase the release of proinflammatory mediators, such as cytokines, by neutrophils and other cellular populations, elevated intracellular concentrations of H 2 O 2 diminish LPS-induced neutrophil activation (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Evidence concerning that TLR plays important roles in cardiovascular pathologies such as especially myocardial IR and atherosclerosis is getting increased [21]. It has been demonstrated that extracellular O 2 -which develops due to Xantine oxidase in IR injury activates neutrophils and induced neutrophil-related proinflammatory response occurs via TLR-4-related mechanisms [22]. In a study conducted with mice, high level of TLR-4 expression was determined in ventricular muscle 4 days after MI and it was reported that protection against myocardial inflammatory injury occurs in TLR-4 knock-out mice [23].…”
Section: Discussionmentioning
confidence: 99%